The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1098/rstb.2020.0424
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive and perceptual correlates of ideological attitudes: a data-driven approach

Abstract: Although human existence is enveloped by ideologies, remarkably little is understood about the relationships between ideological attitudes and psychological traits. Even less is known about how cognitive dispositions—individual differences in how information is perceived and processed— sculpt individuals' ideological worldviews, proclivities for extremist beliefs and resistance (or receptivity) to evidence. Using an unprecedented number of cognitive tasks ( n = 37) and personality surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 101 publications
2
70
1
Order By: Relevance
“…Personality traits have reappeared within wide-ranging analyses of predictors of ordinary political preferences in studies at several countries (Aidt and Raub, 2018;Barceló, 2017;Hibbing, 2021;Wang, 2016;Zmigrod et al, 2021). The mediating role of temperamental traits on political polarization and sectarian partisanship has also been analyzed with illuminating findings 5 (Federico, 2021Finkel et al, 2020;Gotzsche-Astrup, 2019;Hibbing, 2021;Jost, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Personality traits have reappeared within wide-ranging analyses of predictors of ordinary political preferences in studies at several countries (Aidt and Raub, 2018;Barceló, 2017;Hibbing, 2021;Wang, 2016;Zmigrod et al, 2021). The mediating role of temperamental traits on political polarization and sectarian partisanship has also been analyzed with illuminating findings 5 (Federico, 2021Finkel et al, 2020;Gotzsche-Astrup, 2019;Hibbing, 2021;Jost, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with large samples of normative people using self-reports have repeatedly demonstrated strong associations between radical/extremist views and dogmatic intolerance both on political and religious issues Krouwel, 2017, 2019). The predictive capacity of measures based on individual traits for extremist political adscription is now increasingly grounded (Finkel et al, 2020;Hibbing, 2021;Santamaria-Garcia et al, 2021;Zmigrod et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cognitive rigidity and impaired metacognitive awareness, more general difficulties with complex cognitive processing involved in planning and working memory may underlie tendencies to adopt extreme pro-group attitudes. In a data-driven study, Zmigrod and colleagues (2021) administered more than three dozen classic neuropsychological tasks from the cognitive-psychology cannon to investigate the relationships between performance on these tasks and extreme pro-group attitudes. The psychological measures were administered 2 years prior to the ideological questionnaires, which lent a temporal dimension to the analysis: Assessment of psychological traits preceded the assessment of ideological worldviews.…”
Section: Cognitive Underpinnings Of Extreme Political Actionmentioning
confidence: 99%
“…Asterisks indicate variables that were significant predictors of extreme pro-group attitudes, including support for ideological violence against out-groups to protect the in-group (* p < .05, ** p < .01). Adapted from Zmigrod and colleagues (2021), p. 9 in the main article (a) and p. 5 in the Supplemental Material (b).…”
Section: Cognitive Underpinnings Of Extreme Political Actionmentioning
confidence: 99%